PFAS v materialih v stiku z živili - Zajc, Mateja (Papir (Ljubljana), 2021)
Paper and cardboard packaging, which is coated with per- and polyfluorinated alkyl substances (PFAS) in more than half of cases, are replacing disposable plastic. In addition to serious human health concerns resulting from their transfer to food and subsequent ingestion, PFAS in paper products are also retained during composting, and compost from these disposable paper products is dangerous due to high levels of PFAS. This runs counter to the key objectives of banning single-use plastics and has other unexpected effects on health and the environment. Denmark was the first European country to ban the use of PFAS in food contact materials by regulation in July 2020, and in July this year, certain EU Member States, i.e. Germany, Denmark, the Netherlands, Norway and Sweden, notified the European Chemicals Agency (ECHA) of their intention to submit restrictive documentation. EU Member States agree that the use of PFAS causes irreparable damage to the environment and people, which is again reflected in the need to establish uniform regulations for food contact materials in Europe
Keywords: embalaža; environment; food contact; health; okolje; packaging; PFAS; restriction; stik z živili; zdravje